Kekerasan dan Abortus Provocatus - Jacobus Tarigan (Respons: Jurnal Etika Sosial, 2009)
Abortus provocatus is one of the sadistic violent actions that make the fetusasits scapegoat and the victim of violence. It is a criminal action that breaks the law andthemoral values. As many other violence actions that is inherited genetically and sociallyinhuman society, abortus provocatus endangers human life and its enviroment. To preventthis violent action this article suggests that we need education on love and the creation oflove culture.